1995
DOI: 10.1002/bit.260470303
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification of proteins using ligands derived from peptide libraries

Abstract: Peptide libraries can be used to identify ligands that bind specifically to a desired protein. These peptides may have significant advantages as specific ligands for affinity chromatography separations. This article describes the use of one of such peptide, Try-Asn-Phe-Glu-Val-Leu, as a ligand for the purification of S-protein using affinity chromatography. General strategies for peptide immobilization are discussed and the conditions for peptide immobilization to Emphazetrade mark gel are optimized. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 19 publications
(4 reference statements)
0
41
0
Order By: Relevance
“…Released peptides were eluted with 10 μl AcOH/CH 3 CN/H 2 O (3/4/3), and 1 μl sample was loaded onto the sample plate, air dried at room temperature, and then, 1 μl matrix solution (CHCA 4 mg/ml in CH 3 CN/H 2 O (1/1) with 0.1% TFA and doped with serine 20 mM) was added to the spot without mixing. The signal at m/z 1009.6 corresponds to HOCH 2 CO-Leu-Arg-His-Leu-Thr-Asp(Ala-NH 2 )-Ala-Gly-NH 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Released peptides were eluted with 10 μl AcOH/CH 3 CN/H 2 O (3/4/3), and 1 μl sample was loaded onto the sample plate, air dried at room temperature, and then, 1 μl matrix solution (CHCA 4 mg/ml in CH 3 CN/H 2 O (1/1) with 0.1% TFA and doped with serine 20 mM) was added to the spot without mixing. The signal at m/z 1009.6 corresponds to HOCH 2 CO-Leu-Arg-His-Leu-Thr-Asp(Ala-NH 2 )-Ala-Gly-NH 2 …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows an example of a MALDI mass spectrum and MALDI tandem mass spectrum of peptides eluted from one bead of the combinatorial library. The signal at m/z 1009.6 corresponds HOCH 2 CO-LeuArg-His-Leu-Thr-Asp(Ala-NH 2 )-Ala-Gly-NH 2 Peptide sequences could be deduced from the tandem mass spectra (Figure 1 After library screening and MS sequencing, selected peptide ligands are resynthesised in larger amounts to study their performance for their intended use. In order to assure cyclic ligand stability, the Ala-glycolamidic ester bond can be replaced by an Ala-Gly amide bond by assembling Gly instead of glycolic acid.…”
Section: Resultsmentioning
confidence: 99%
“…When this is translated to an affinity support (such as CNBractivated Sepharose) the orientation of the ligand is reversed and its ability to bind antibody is severely reduced. Other researchers have found that orienta- tion of small peptide ligands may be irrelevant to purification performance (31); therefore, the problem may be system specific. In our approach, the hydrophobic phenylalanine and leucine residues are critical in the MAb4155-peptide interaction, suggesting the requirement to be spaced away from the surface of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of a peptide to an antibody paratope is ultimately controlled by the complementarity of the surfaces (31). This includes charge-charge and hydrophobic interactions as well as three-dimensional conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Short peptides are widely used as ligands in affinity chromatography purification of proteins [1,2]. However, peptidases and proteases present in the crude sample may degrade immobilized peptides, shortening the affinity support useful life.…”
Section: Introductionmentioning
confidence: 99%